Oxygen isotopic evidence that Gale crater, Mars, was home to an Early Hesperian water reservoir that underwent significant evaporation - Amy E. Hofmann; P. Douglas Archer; Amy C. McAdam; Brad Sutter; Thomas F. Bristow; John M. Eiler; Christopher R. Webster; Gregory J. Flesch; Abigail A. Fraeman; Heather B. Franz; Christopher H. House; Elizabeth B. Rampe; et al. (Proceedings of the National Academy of Sciences, 2025)
Simultaneous measurements of HDO, H 2 18 O, and H 2 16 O in water evolved during pyrolysis of powdered rock samples acquired by the Curiosity rover within Gale crater’s clay-bearing units indicate extreme and variable heavy-isotope enrichments averaging ~4.5 times the D/H ratio and ~1.03 times the 18 O/ 16 O ratio of terrestrial seawater. These enrichments are recorded in water desorbed from mineral surfaces and evolved from poorly crystalline phases, hydrated salts, jarosite, and clays. All evolved waters are deuterium-enriched relative to common terrestrial waters, reflecting hydrogen loss to space. Because oxygen in structurally bound hydroxyl groups is least likely to exchange with other sources over geologic timescales, we focus on oxygen in water evolved during dehydroxylation of smectite clays. Several samples have 18 O/ 16 O ratios commensurate with precipitation from, or near-complete equilibration with, water moderately 18 O-enriched relative to terrestrial meteoric waters—consistent with other evidence that Mars’s hydrosphere is basically like Earth’s in terms of oxygen isotopes. Unlike hydrogen, oxygen atmospheric escape did not lead to extreme 18 O enrichments on Mars. Locally, however, most Gale smectites’ 18 O/ 16 O values require a pronounced 18 O-enrichment of their parental waters. On Earth, the most extreme 18 O enrichments in surface waters are found in closed basins having undergone significant evaporative loss into a low-humidity atmosphere, and the 18 O/ 16 O of authigenic clay minerals formed in these environs reflect those enrichments. A similar process acting on the hydrologic reservoir local to Gale at the time of clay formation and early diagenesis is a plausible explanation for the distinctive oxygen isotopic compositions of these clays.